Evaluating the Alignment of the MBKM S-1 PIAUD Curriculum with Raudatul Atfal Institution Needs - Huliyah, Muhiyatul; Umayah, Umayah; Fauzia, Wulan (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
The MBKM (Merdeka Belajar Kampus Merdeka) curriculum aims to improve higher education institutions' ability to produce graduates ready to face challenges in modern technology, science, and society. This study aims to evaluate the MBKM undergraduate Islamic Early Childhood Education (PIAUD) curriculum, focusing on its alignment with the needs of Raudatul Atfal (RA) institutions. Questionnaires were distributed to selected RA institutions using a comprehensive evaluation process. Most of the feedback indicated that the curriculum met professional standards very well, although there were some differences of opinion. A thorough analysis of the responses showed that most stakeholders appreciated the benefits of the curriculum but noted some inconsistencies in its relevance and pointed out areas for improvement. The curriculum aligns with industry expectations and can serve as a model for other programs. The study confirms its effectiveness and provides insights for education policymakers adapting to changing industry standards.